Synaptopathy Mechanisms in ALS Caused by C9orf72 Repeat Expansion - Nishimura, Agnes L.; Arias, Natalia (Frontiers in Cellular Neuroscience, 2021)
Amyotrophic Lateral Sclerosis (ALS) is a complex neurodegenerative disease caused by degeneration of motor neurons. Synapse dysfunction is a key feature in ALS and underlie synaptic plasticity alterations where mitochondria play a central role in its regulation. ALS disease features include accumulation of misfolded proteins, glutamate excitotoxicity, mitochondrial dysfunction at distal axon terminals and neuronal cytoskeleton changes. These features are consistent with a proposed pathogenic mechanism of synaptic diseases. Synergies between loss of C9orf72 functions and gain of function by toxic effects of repeat expansions also contribute to C9orf72-mediated pathogenesis. However, the impact of haploinsufficiency of C9orf72 on neurons and in synaptic functions requires further examination. Current therapies are severely limited owing to a poor understanding of the mechanisms of C9orf72 pathobiology. In this review, we provide a conceptual framework for assessing the putative involvement of C9orf72 as a synaptopathy and we explore the underlying and common disease mechanisms with other neurodegenerative diseases. Furthermore, we explore the tangible possibility of early therapeutic interventions targeting synaptic dysfunctions. Finally, we reflect on the major challenges of understanding C9orf72-ALS as a synaptopathy focusing on integrating mitochondrial and neuronal cytoskeleton degeneration as biomarkers and potential targets to treat ALS neurodegeneration.